An efficient simple reaction type water turbine for pico hydro application - Md Basar, Mohd Farriz; Mohd Rais, Nurul Ashikin; Azahar, Arman Hadi; Abd Gani, Shamsul Fakhar (Asian Research Publishing Network (ARPN), 2022)
The focus of the study is on the performance characteristics of an efficient Z-Blade turbine, which is classed as a simple reaction type water turbine that may be used in pico hydro applications. As a result, the geometrical design of the turbine as well as experimental results are provided. The test unit's applicability in low-head, low-flow situations was also investigated in this study. Using the governing equations that have been created using the principles of conservation of mass, momentum, and energy, the Z-Blade turbine has been investigated for an ideal and practical condition. Using various frictional losses factors (k-factors) for different working heads, the correlation between rotor diameter, angular speed, flow rate, power output, and efficiency is illustrated and analysed with reference to experimental data. The data were compared to theoretical results using inlet water pressures ranging from 30 to 50 kPa, turbines with rotor diameters ranging from 0.4 to 1.8 metres, and a nominal PVC pipe diameter of 25 mm (1”). This hydraulic reaction turbine, which has a simple fabrication method, can produce high power output and minimal power loss with an overall energy conversion efficiency of 68 percent under low-head low-flow water resources.